Pengaruh Model Pembelajaran dan Kesadaran Metakognisi terhadap Hasil Belajar Peserta Didik - Sonyinga, Desma; Danial, Muhammad; Herawati, Netti (Chemistry Education Review (CER), 2019)
The study is quasi experiment which aims at examining the influence of learning model and metacognition awareness on learning autocomes of grade X at SMA Islam in Ternate city on chemistry Bond subject. The study employed 2x2 factorial research desaign. Samples consisted of two classes selected by employing random sampling technique and obtained grade X IPA 1 as the experiment class 1 taught by using guided inquiry learning model and grade X IPA 2 as experiment class 2 taught by using problem-based learning model. The research instruments used questionnaire of metacognition awareness inventory and learning result test. Data obtained were analyzed inferentially and descriptively. The results of inferential analysis reveal that (1) the learning model gives influence on learning outcomes with significant score of 0.01<0.05, (2) The metacognition awareness give influence on learning outcomes with significant score 0.008 < 0.05, (3) there is interaction of learning model and metacognition awareness, proved by the significant score 0.014 < 0.05. Then, the results of descriptive analysis indicate that (1) the mean score of learning outcomes taught using guided inquiry learning model is higher than problem-based learning model, (2) the mean score of learning outcomes with high metacognition awareness is higher than the mean score of learning outcomes with low metacognition awareness, (3) there is interaction between learning model and metacognition awareness in influencing learning outcomes of grade X IPA at SMA Islam in Ternate city. Therefore, there is influence between learning model and metacognition awareness on learning outcomes of grade X at SMA Islam in Ternate city on Chemistry Bond subject.